Profile and Management Outcomes of Fireworks-Related Eye Injuries in Saudi Arabia: A 16-Year Retrospective Study - AlGhadeer H (Dove Medical Press, 2021)
Huda AlGhadeer,1 Rajiv Khandekar2 1Department of Emergency, King Khaled Eye Specialist Hospital, Riyadh, Saudi Arabia; 2Department of Research, King Khaled Eye Specialist Hospital, Riyadh, Saudi ArabiaCorrespondence: Huda AlGhadeerDepartment of Emergency, King Khaled Eye Specialist Hospital, PO Box 7191, Riyadh, 11462, Saudi ArabiaTel +966 1 4821234 ext 2500Fax +966 1 4821234 ext 3727Email hghadeer@kkesh.med.saBackground: Fireworks are a culturally significant part of celebrations in many parts of the world but can lead to blinding injuries.Objective: To decipher the profile and management outcomes of fireworks-related eye injuries at a tertiary eye hospital in central Saudi Arabia.Methods: This was a retrospective review of cases with fireworks-related eye injuries managed at our institution between 2003 and 2019. Demographic information, clinical features at presentation, mode of management, and visual outcome were evaluated at the last follow-up.Results: A total of 155 eyes of 150 patients with a median age of 10 years [127 male (84.7%) and 69 (46%) right eyes, 76 (50.7%) left eyes, and 5 patients with bilateral injury] were enrolled for the study. Among the injured individuals, 59 (39.3%) were bystanders and 91 (60.7%) had ignited the fireworks. The fireworks included bangers (53; 35.3%), rockets in bottle (42; 28%), firecrackers (41; 27.3%). Closed globe injury (CGI) was the most common type of eye injury (100; 64.5% eyes) while Open globe injury (OGI) was noted in (55; 35.5% eyes). Management used for treatment included penetrating injury repair (55; 35.5%), lens removal/lens implant (51; 32.9%). Corrected distance visual acuity obtained after 6 months was 20/20 to 20/60 (74; 47.7%), 20/70 to 20/200 in (31; 20%), < 20/200 to 20/400 in (9; 5.8%) and < 20/400 in (41; 26.5%) eyes. Treatment was able to restore vision and salvage blindness in 50 (32.3%) eyes.Conclusion: Mainly males were found to suffer from fireworks-related eye injuries and the main fireworks responsible for them were bangers. Visual disability remained in one-third of the treated patients.Keywords: fireworks, injuries, ocular trauma, visual loss